Análisis, diseño e implementación de un sistema de seguimiento a egresados y graduados de la Universidad Nacional de Loja. - Romero Armijos, Iralda Soledad (2013)
This project of career completion (PFC) includes the analysis, design and implementation of a monitoring system to non graduates and graduates (SISEG) to the National University of Loja, which allows to update alumni data, survey administration, promote academic events and labor meetings, managing the careers professionals profiles, alumni directory and other activities concerning SISEG that will be discovered in this document. Regarding to the theoretical support described in the literature review section, information was collected regarding concepts defined in this PFC such as tracing of non graduates and graduates; as well as defined development tools used. To perform the analysis, interpretation and critical evaluation of this PFC were used data collection techniques and appropriate scientific methods that were applied to all actors involved in the SISEG; also were used XP (Extreme Programming) as a software development methodology, same that allows an agile, fast, flexible and high quality development, besides makes it easy to work directly with the user. The SISEG was implemented in PHP using the CodeIgniter framework, whose pattern of development is the MVC (Model View Controller), as manager of the database was used MySql. In the results section was detailed the SISEG developing process, following the development methodology used, in this way are described the system requirements, user stories, architecture design, diagrams like class, use cases among others to achieve the expected results, so also were documented the design of the user interface and implementation, testing and analysis of results. The discussion indicates how each of the goals set at the beginning of the project was reached. Finally we present the conclusions obtained after finishing this project and includes recommendations based on the experience gained during the development process of this PFC.